The Effect of Yaker's Strategy on The Achievement of Fifth Grade Literary Students on The Achievement of Fifth Grade Literary Students In Philosophy and Psychology and The Development of Their Cognitive Curiosity - Ammar Sweid (Indonesian Journal Publisher, 2025)
The current research aims to study